Pharmacokinetics of neratinib during coadministration with lansoprazole in healthy subjects. (16th October 2016) - Keyvanjah, Kiana; DiPrimeo, Daniel; Li, Ai; Obaidi, Mohammad; Swearingen, Dennis; Wong, Alvin
Abstract : Aims: To evaluate the effect of lansoprazole, a proton‐pump inhibitor, on the absorption, pharmacokinetics, and safety of neratinib, a pan‐HER tyrosine kinase inhibitor, in healthy subjects. Methods: This was an open‐label, two‐period, fixed‐sequence study. Fifteen healthy adult subjects received a single oral dose of neratinib 240 mg (Period 1), followed by a washout period, then oral lansoprazole 30 mg once daily for 7 days and a single dose of neratinib 240 mg on Day 5 (Period 2). Pharmacokinetic sampling was performed for 72 h following each neratinib dose. Plasma neratinib concentration–time data were analysed using noncompartmental methods. Geometric mean ratios for AUC0–t, AUC0–inf, and peak plasma concentrations (Cmax ) for neratinib plus lansoprazole vs. neratinib were used to assess the magnitude of the drug–drug interaction if the 90% confidence intervals were outside 80.00–125.00%. Results: Neratinib geometric least‐squares mean (LSM) Cmax was reduced from 84.5 ng ml −1 with neratinib alone to 24.5 ng ml −1 with neratinib plus lansoprazole. The extent of exposure to neratinib was also decreased: geometric LSM AUC0–t was 1478 ng ml −1  h with neratinib vs. 426 ng ml −1  h with neratinib plus lansoprazole, and geometric LSM AUC0–inf was 1557 ng ml −1  h vs. 542 ng ml −1  h, respectively. Mean t½ was similar with both treatments (approximately 14 h). Geometric mean ratios 90% confidence intervals for AUC0–t, AUC0–inf and Cmax fell outside the prespecified equivalence range (80.0–125.0%). Treatment‐emergent adverse events, all mild, were reported by five (33%) subjects. Conclusions: Coadministration of lansoprazole with neratinib reduced the rate and extent of neratinib exposure in healthy subjects.